Inflammation and immunity in the pathogenesis of hypoxic pulmonary hypertension - Ye, Yi; Xu, Qiying; Wuren, Tana (Frontiers in Immunology, 2023)
Hypoxic pulmonary hypertension (HPH) is a complicated vascular disorder characterized by diverse mechanisms that lead to elevated blood pressure in pulmonary circulation. Recent evidence indicates that HPH is not simply a pathological syndrome but is instead a complex lesion of cellular metabolism, inflammation, and proliferation driven by the reprogramming of gene expression patterns. One of the key mechanisms underlying HPH is hypoxia, which drives immune/inflammation to mediate complex vascular homeostasis that collaboratively controls vascular remodeling in the lungs. This is caused by the prolonged infiltration of immune cells and an increase in several pro-inflammatory factors, which ultimately leads to immune dysregulation. Hypoxia has been associated with metabolic reprogramming, immunological dysregulation, and adverse pulmonary vascular remodeling in preclinical studies. Many animal models have been developed to mimic HPH; however, many of them do not accurately represent the human disease state and may not be suitable for testing new therapeutic strategies. The scientific understanding of HPH is rapidly evolving, and recent efforts have focused on understanding the complex interplay among hypoxia, inflammation, and cellular metabolism in the development of this disease. Through continued research and the development of more sophisticated animal models, it is hoped that we will be able to gain a deeper understanding of the underlying mechanisms of HPH and implement more effective therapies for this debilitating disease.